2011
DOI: 10.1371/journal.pone.0027063
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Upregulation in E-Cadherin-Negative Esophageal Cancers Results in Cell Invasion

Abstract: E-cadherin is frequently lost during epithelial-mesenchymal transition and the progression of epithelial tumorigenesis. We found a marker of epithelial-mesenchymal transition, CD44, upregulated in response to functional loss of E-cadherin in esophageal cell lines and cancer. Loss of E-cadherin expression correlates with increased expression of CD44 standard isoform. Using an organotypic reconstruct model, we show increased CD44 expression in areas of cell invasion is associated with MMP-9 at the leading edge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
1
29
0
1
Order By: Relevance
“…Le Bras et al (30) revealed that activin A increases cell invasion through CD44 upregulation following E-cadherin loss and increased CD44 expression in areas of cell invasion associated with MMP-9. In addition, activin A induced in vitro invasion of esophageal squamous cell carcinoma cells, which was accompanied by an increased MMP-2 and MMP-9 in esophageal squamous cell carcinoma cells samples (28).…”
Section: Discussionmentioning
confidence: 99%
“…Le Bras et al (30) revealed that activin A increases cell invasion through CD44 upregulation following E-cadherin loss and increased CD44 expression in areas of cell invasion associated with MMP-9. In addition, activin A induced in vitro invasion of esophageal squamous cell carcinoma cells, which was accompanied by an increased MMP-2 and MMP-9 in esophageal squamous cell carcinoma cells samples (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, these reports did not describe the significance of podoplanin membrane expression that we focused on in this study. We demonstrated two different evaluations, namely, intensity and localization, in the present change by which epithelial cells lose their polarity, epithelial markers, such as E-cadherin, and obtain migratory factors, such as vimentin and snail which is one of the transcription factors playing an important role in epithelial-to-mesenchymal transition (9,17,26,31,32). Vimentin expression is one of the good indicators for epithelial-to-mesenchymal transition of carcinoma, which is considered to be associated with aggressive phenotypes with invasive/ metastatic potential (16).…”
Section: Relationships Between Podoplanin Intensity and Localizationmentioning
confidence: 97%
“…Afterward, p75NTR was introduced as a marker to identify esophageal cancerous cells with self-renewal and enhanced drug resistance [76]. Further studies characterized esophageal CSCs and proposed CD44 [77][78][79][80][81], CD133, CXCR4 [82], CD90 [83], and CD15 [78] as markers for esophageal stemlike cancer cells. ALDH1 activity has also been reported as a CSC marker in ESCC and esophageal adenocarcinoma (EAC), because ALDH1 + cells were highly proliferative and chemoresistant [84,85].…”
Section: Esophagusmentioning
confidence: 99%
“…Furthermore, the expression of OCT4 and SOX2 was significantly associated with higher histological grade and poorer survival of ESCC [93,94]. In addition, expression of CD133 [82] and CD44 [79,95,96], specifically CD44v6 [97,98], was associated with clinicopathological features of ESCC and EAC, although a number of studies reported contradictive results [99][100][101]. In addition, BMI1 overexpression was correlated to advanced pathological stage and lymph node metastasis in ESCC and EAC [102,103].…”
Section: Esophagusmentioning
confidence: 99%